2002
DOI: 10.1016/s1534-5807(02)00125-9
|View full text |Cite
|
Sign up to set email alerts
|

Sly1 Binds to Golgi and ER Syntaxins via a Conserved N-Terminal Peptide Motif

Abstract: Sec1/munc18-like proteins (SM proteins) and SNARE complexes are probably universally required for membrane fusion. However, the molecular mechanism by which they interact has only been defined for synaptic vesicle fusion where munc18 binds to syntaxin in a closed conformation that is incompatible with SNARE complex assembly. We now show that Sly1, an SM protein involved in Golgi and ER fusion, binds to a short, evolutionarily conserved N-terminal peptide of Sed5p and Ufe1p in yeast and of syntaxins 5 and 18 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
264
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 186 publications
(290 citation statements)
references
References 59 publications
19
264
0
7
Order By: Relevance
“…Because the N-terminal sequence of various syntaxins has been previously implicated in interactions with SM proteins that are compatible with SNARE complex formation (20,21), we examined the role of the syntaxin-1A N-terminal sequence in the Munc18-1/SNARE complex interaction. Remarkably, SNARE complexes with a syntaxin-1A fragment containing a short N-terminal truncation (syntaxin-1A 10 -253 ) did not produce a significant shift in the mobility of Munc18-1 in gel filtration, showing that the syntaxin-1A N-terminal sequence is critical for binding of Munc18-1 to the SNARE complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the N-terminal sequence of various syntaxins has been previously implicated in interactions with SM proteins that are compatible with SNARE complex formation (20,21), we examined the role of the syntaxin-1A N-terminal sequence in the Munc18-1/SNARE complex interaction. Remarkably, SNARE complexes with a syntaxin-1A fragment containing a short N-terminal truncation (syntaxin-1A 10 -253 ) did not produce a significant shift in the mobility of Munc18-1 in gel filtration, showing that the syntaxin-1A N-terminal sequence is critical for binding of Munc18-1 to the SNARE complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that SNAREs and SM proteins interact by diverse mechanisms: Munc18-1 (and likely Munc18-2) was shown to bind only to the closed conformation of syntaxin outside of the SNARE complex (7,8,16); Sly1, Vps45, and Munc18c were found to bind to the N-terminal sequences of their respective cognate syntaxins independent of whether they are in SNARE complexes (20,21,25,26,33); yeast Sec1p was observed to bind only to assembled SNARE complexes without participation of the N-terminal sequence of syntaxins Sso1/2p (18,19); and Vps33p was found to bind to SNARE complexes by interacting with the PX domain of Vam7p (27,28). Faced with this diversity of interactions and the fact that, among SM proteins, only Munc18-1 did not bind to assembled SNARE complexes, we have reinvestigated how Munc18-1 interacts with SNARE proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because N-terminal regions in Sec22p and other SNARE proteins are required for their proper intracellular targeting (17)(18)(19)(20), it seems probable that signals within these regions will interact with distinct coat protein complexes in addition to COPII. Such differential interactions are likely to govern intracellular location and therefore contribute to the fidelity of membrane fusion reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal domains of SNARE proteins display significant diversity and appear to govern SNARE protein activity and distribution. For example, the N-terminal domain of the syntaxin-like SNARE proteins, such as neuronal syntaxin1 and yeast Sso1p, fold into three-helix bundles and inhibit SNARE pairing when folded back against their SNARE domains ( [17][18][19][20]. The structure of the N-terminal domain of a non-syntaxin yeast SNARE, Ykt6p, resembles the overall fold of the actin regulatory protein, profilin.…”
mentioning
confidence: 99%